Farm Pond Technology for Enhancing Crop Productivity in Bhal Area of Gujarat - A Case Study - Vora, M D; Solanki, H B; Bhoi, K l (Journal of Agricultural Engineering, 2008)
A case study on utilizing farm pond technology for enhancing crop productivity in Bhal and Coastal Zone of Gujarat over a period of ten years was undertaken at Regional Agricultural Research Station, Arnej. The groundwater of this area is saline and canal irrigation is quite limited. Therefore, rainwater harvesting is the only source for increasing productivity of crops in this region through supplemental or life saving irrigation. Study revealed 30 to 50% increment in production of wheat, gram and cumin crops with one supplementary irrigation of 6 cm depth. Up to more than 10,000 m³of rainwater could be harvested through gravitational force only in a farm pond of 40,000 m³ capacity. In absence of adequate natural drainage, the farm pond at the station helped in draining excess rainwater stagnated into fields due to flat topography of land. Hence, additional drainage provided by pond made sowing of kharif crops possible. Expecting 10,000 m³ water yield subtracting evaporation and seepage losses at the rate of 33.44% as observed, 6,656 m³ water per year will be available for irrigation which may bring 10 ha of land under one supplementary irrigation 6 cm depth. It was estimated that the initial investment in form of cost on farm pond can be recovered within 4 years only. Net additional income generated from pond water irrigation was three times higher than the additional cost. An additional income of Rs. 4,235 per ha was ensured from irrigating conventional crops only.